2021
DOI: 10.21203/rs.3.rs-877485/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of External Dynamic Disturbances And Structural Plane On Rock Fracturing Around Deep Underground Cavern

Abstract: The occurrence of disasters in deep mining engineering has been confirmed to be closely related to the external dynamic disturbances and geological discontinuities. Thus, a combined finite-element approach was employed to simulate the failure process of an underground cavern, which provided insights into the failure mechanism of deep hard rock affected by factors such as the dynamic stress-wave amplitudes, disturbance direction, and dip angles of the structural plane. The crack-propagation process, stress-fiel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At the fourth stage of the process, the process abruptly declined, and at the fifth stage, there was a slight increase and decrease. Xu et al suggested that changes in the correlation dimension are indicators of crack emergence and evolution in rock samples 59 – 64 . According to Li et al, when coal under loading reaches a specific stress level, the correlation dimension of AE shows a downward trend, and the failure rate of coal reflects the fractal law as coal failure progresses.…”
Section: Discussionmentioning
confidence: 99%
“…At the fourth stage of the process, the process abruptly declined, and at the fifth stage, there was a slight increase and decrease. Xu et al suggested that changes in the correlation dimension are indicators of crack emergence and evolution in rock samples 59 – 64 . According to Li et al, when coal under loading reaches a specific stress level, the correlation dimension of AE shows a downward trend, and the failure rate of coal reflects the fractal law as coal failure progresses.…”
Section: Discussionmentioning
confidence: 99%
“…With in large-scale strategic engineering of deep rock mass in China, ensuring stability of a deep rock mass structure and preventing catastrophes have become the first priority. The existing research shows: Deep rock mass has obvious rheological characteristics, and it is very easy to aggravate its rheological state due to blasting, earthquake and other disturbances, thus causing instability and failure of deep rock mass (Feng et al, 2022;Wiatowski et al, 2021). Therefore, the influence of load on deep rock masses cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In the fourth stage, 𝐷 declined, and in the fifth stage, it decreased or increased little. According to Xu et al, the change in correlation dimension can well reflect the beginning and evolution of micro-cracks in rock samples[63][64][65][66][67][68]. According to Li et alwhen coal under loading reaches a specific stress level, the correlation dimension of AE shows a downward trend, and the failure rate of coal reflects the fractal law as coal failure progresses.…”
mentioning
confidence: 99%